Covalent organic framework cladding on peptide-amphiphile-based biomimetic catalysts - Kumar Mahato, Ashok; Pal, Sumit; Dey, Kaushik; Reja, Antara; Paul, Satyadip; Shelke, Ankita; Ajithkumar, Thalasseril G.; Das, Dibyendu; Banerjee, Rahul (Journal of the American Chemical Society, 2023)
Peptide-based biomimetic catalysts are promising materialsforefficient catalytic activity in various biochemical transformations.However, their lack of operational stability and fragile nature innon-aqueous media limit their practical applications. In this study,we have developed a cladding technique to stabilize biomimetic catalystswithin porous covalent organic framework (COF) scaffolds. This methodologyallows for the homogeneous distribution of peptide nanotubes insidethe COF (TpAzo and TpDPP) backbone, creating strong noncovalent interactionsthat prevent leaching. We synthesized two different peptide-amphiphiles,C10FFVK and C10FFVR, with lysine (K) and arginine(R) at the C-termini, respectively, which formed nanotubular morphologies.The C10FFVK peptide-amphiphile nanotubes exhibit enzyme-likebehavior and efficiently catalyze C-C bond cleavage in a buffermedium (pH 7.5). We produced nanotubular structures of TpAzo-C10FFVK and TpDPP-C10FFVK through COF claddingby using interfacial crystallization (IC). The peptide nanotubes encasedin the COF catalyze C-C bond cleavage in a buffer medium aswell as in different organic solvents (such as acetonitrile, acetone,and dichloromethane). The TpAzo-C10FFVK catalyst,being heterogeneous, is easily recoverable, enabling the reactionto be performed for multiple cycles. Additionally, the synthesis ofTpAzo-C10FFVK thin films facilitates catalysis inflow. As control, we synthesized another peptide-amphiphile, C10FFVR, which also forms tubular assemblies. By depositingTpAzo COF crystallites on C10FFVR nanotubes through IC,we produced TpAzo-C10FFVR nanotubular structuresthat expectedly did not show catalysis, suggesting the critical roleof the lysines in the TpAzo-C10FFVK.

Hierarchical covalent organic framework-foam for multi-enzyme tandem catalysis - Paul, Satyadip; Gupta, Mani; Dey, Kaushik; Mahato, Ashok Kumar; Bag, Saikat; Torris, Arun; Gowd, E. Bhoje; Sajid, Hasnain; Addicoat, Matthew A.; Datta, Supratim; Banerjee, Rahul (Chemical Science, 2023)
Covalent organic frameworks (COFs) are ideal host matrices for biomolecule immobilization and biocatalysis due to their high porosity, various functionalities, and structural robustness. However, the porosity of COFs is limited to the micropore dimension, which restricts the immobilization of enzymes with large volumes and obstructs substrate flow during enzyme catalysis. A hierarchical 3D nanostructure possessing micro-, meso-, and macroporosity could be a beneficial host matrix for such enzyme catalysis. In this study, we employed an in situ CO2 gas effervescence technique to induce disordered macropores in the ordered 2D COF nanostructure, synthesizing hierarchical TpAzo COF-foam. The resulting TpAzo foam matrix facilitates the immobilization of multiple enzymes with higher immobilization efficiency (approximately 1.5 to 4-fold) than the COF. The immobilized cellulolytic enzymes, namely beta-glucosidase (BGL), cellobiohydrolase (CBH), and endoglucanase (EG), remain active inside the TpAzo foam. The immobilized BGL exhibited activity in organic solvents and stability at room temperature (25 degrees C). The enzyme-immobilized TpAzo foam exhibited significant activity towards the hydrolysis of p-nitrophenyl-beta-d-glucopyranoside (BGL@TpAzo-foam: K-m and V-max = 23.5 +/- 3.5 mM and 497.7 +/- 28.0 mu M min(-1)) and carboxymethylcellulose (CBH@TpAzo-foam: K-m and V-max = 18.3 +/- 4.0 mg mL(-1) and 85.2 +/- 9.6 mu M min(-1) and EG@TpAzo-foam: K-m and V-max = 13.2 +/- 2.0 mg mL(-1) and 102.2 +/- 7.1 mu M min(-1)). Subsequently, the multi-enzyme immobilized TpAzo foams were utilized to perform a one-pot tandem conversion from carboxymethylcellulose (CMC) to glucose with high recyclability (10 cycles). This work opens up the possibility of synthesizing enzymes immobilized in TpAzo foam for tandem catalysis.

Chirality transfer from covalent organic framework nanotubes to covalent organic framework films via chirality induction crystallization - Bag, Saikat; Chatterjee, Debasmita; Mahapatra, Rohan; Sasmal, Himadri Sekhar; Khatua, Arindam; Giri, Madhurima; Paul, Satyadip; Shelke, Ankita; Almasoud, Najla; Alomar, Taghrid S.; Ajithkumar, Thalasseril G.; Sen Gupta, Sayam; et al. (Advanced Materials, 2026)
We report the synthesis of homochiral crystalline covalent organic framework (COF) films that combine rigidity and porosity, offering significant promise for heterogeneous asymmetric catalysis. We prepared enantiopure COF films from achiral diamine and trialdehyde precursors using a chiral induction crystallization strategy. A Schiff-base reaction, catalyzed by a chiral acid, namely (R)- and (S)-camphorsulfonic acids (CSA) generated a beta-ketoenamine backbone with induced chirality. (R)- and (S)-camphorsulfonic acids direct the diamine-trialdehyde condensation and induce chirality during the nucleation of COF nanotubes, enabling their periodic arrangement and the formation of homochiral thin films. We successfully synthesized six distinct COF films with three different backbone functionalities: R-, S-TpAzo; R-, S-TpDPP; and R-, S-TpBDMe2, using the two enantiomers of the chiral camphorsulfonic acids. All films displayed strong circular dichroism signals and pronounced Cotton effects, confirming their enhanced enantiopurity. Both R- and S-TpAzo films exhibited the highest crystallinity, long-range order, and permanent porosity, making them particularly well-suited for catalytic applications. To demonstrate their utility, we encapsulated a bioinspired catalyst, (Et4N)2[FeIII(Cl)bTAML], within the chiral channels of the R- and S-TpAzo films. The resulting composite created a robust heterogeneous catalytic platform for the asymmetric epoxidation of alkenes, achieving excellent activity and enantioselectivity under ambient conditions.
Keywords: chiral induction; covalent organic framework nanotube; covalent organic framework thin film; heterogeneous catalysis